Absence of α- and β-dystroglycan is associated with Walker-Warburg syndrome. (26th May 2015) - Riemersma, Moniek; Mandel, Hanna; van Beusekom, Ellen; Gazzoli, Isabella; Roscioli, Tony; Eran, Ayelet; Gershoni-Baruch, Ruth; Gershoni, Moran; Pietrokovski, Shmuel; Vissers, Lisenka E.; Lefeber, Dirk J.; Willemsen, Michèl A.; et al.
<x xml:space="preserve">Abstract</x> Objective: To identify the underlying genetic defect in 5 patients from a consanguineous family with a Walker-Warburg phenotype, together with intracranial calcifications. Methods: Homozygosity mapping and exome sequencing, followed by Sanger sequencing of the obtained candidate gene, was performed. Expression of the candidate gene was tested by reverse transcription PCR. Patient fibroblasts were converted to myotubes, and the expression and function of dystroglycan was tested by Western blotting. Results: We detected a homozygous loss-of-function frameshift mutation in the DAG1 gene and showed that this mutation results in a complete absence of both α- and β-dystroglycan. Conclusions: A loss-of-function mutation in DAG1 can result in Walker-Warburg syndrome and is not embryonic lethal.